Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

-2x^2+6x+1=-3x^2 solve to the nearest tenth

Sagot :

Step-by-step explanation:

The given equation is :

[tex]-2x^2+6x+1=-3x^2[/tex]

Taking all the terms to one side of the equation i.e.

[tex]-2x^2+6x+1+3x^2=0\\\\x^2+6x+1=0[/tex]

It is a quadratic equation of the form [tex]ax^2+bx+c=0[/tex] whose solution is given by :

[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]

Here, a = 1, b = 6 and c = 1

Put all the values,

[tex]x=\dfrac{-6\pm \sqrt{6^2-4(1)(1)}}{2(1)}\\\\x=-0.171\ and\ x=-5.82[/tex]

Hence, this is the required solution.